Management of Pulp and Paper Mill Waste - Bajpai, Pratima (Springer, 2015)
The management of wastes, in particular of industrial waste, in an economically and environmentally acceptable manner is one of the most critical issues facing modern industry, mainly due to the increased difficulties in properly locating disposal works and complying with even more stringent environmental quality requirements imposed by legislation. The development of innovative systems to maximize recovery of useful materials and/or energy in a sustainable way has become necessary. The significant residual waste streams from pulp and paper mills include wastewater treatment sludges, lime mud, lime slaker grits, green liquor dregs, boiler and furnace ash, scrubber sludges and wood processing residuals. Pulp and paper mill industries are always associated with disposal problem of highly contaminated sludge or bio-solids. In countries with large scale Pulp and paper production, the huge amount of waste generated has prompted the government and industries to find new use of these bio-solids. Paper mill sludges have a net environmental advantage over sewage sludges in that they are nearly pathogen free;